Factors influencing dogs' stress level in the waiting room at a veterinary clinic - Hernander, Louise (SLU/Dept. of Animal Environment and Health (until 231231), 2008)
A number of 110 dogs were observed during their whole time in the waiting room at a veterinary clinic and the dogs' stress level was recorded in three different events; entrance, wait and weighing. One of the aims of this study was to investigate if the gender of the dog had any impact on the dog's stress-related behaviour in the waiting room. This had however no significant influence, suggesting that female and male dogs show an equal amount of stress. Another goal was to establish if the gender of the dog owner influenced the dogs' stress level. No difference between male and female owners could be detected. However the result showed that dogs who is accompanied by a female and a male owner as a couple were more likely to have a higher stress level when entering the clinic than dogs accompanied by a single person, and a similar result was found with regard to the time in the waiting room. Thirdly, dogs that recently had been to the clinic had significantly higher stress value in the waiting room. Also the time in the waiting room itself was analyzed for its impact on the dogs' stress level in comparison with the stress value at the entrance, and the result showed that a vast majority of dogs displayed a decrease in stress during the wait. Finally the weighing of the dogs was analysed for its influence on the dogs' stress level compared to the stress level achieved during the wait, and it showed that a majority of dogs displayed an increase in stress during the weighing. This study suggests that the time in the waiting room is beneficial to the dogs since they get a chance to relax prior to the meeting with the veterinarian. It also suggests that it would be preferable to weigh the dogs right after the registration at the reception desk and then let the dog sit down and wait continuously until it is called up, instead of the current proceeding where the dogs is weighed just before it is time to meet the veterinarian. By taking these adjustments under consideration the welfare of the dogs in the waiting room could probably be improved by small means.